China's Rural-Urban Migration and Its Impact on Economic Development - Zhang, Yuzhe (Université d'Ottawa | University of Ottawa, 2013)
Since the initiation of the well-known economic reform and openingup policy in 1978, hundreds of millions of Chinese rural labourers have left the countryside to work in towns and cities. This biggest labour flow in the world history has not been fully studied due to limited data availability. This paper investigates some major perspectives in terms of rural-to-urban migration in China, including the determinants of migration and its impacts on urbanization and economic development. The main findings can be summarized in the following points. With respect to the determinants, the perceived income differentials between rural and urban areas are the primary source of internal population mobility. Age, gender, dependent children and education level significantly affects decisions to migrate. Referring to the impacts of the labour flow, cityward migration has been a great contribution to economic growth and a dominant source of growth of the urbanization. The huge flow of rural labour disrupts agricultural production, but positively affects per capita income of rural households through remittances, which can further catalyze income growth in self-employed activities in the long run.